Empowering Maluku Communities: Participatory Strategies for Sustainable Local Development - Muhammad Idul Launuru; Ain Nadirah Binti Romainor; Muhammad Rijal (Institute of Multidisciplinary Research and Community Service, 2026)
This study examines strategies to empower communities in Maluku Province, Indonesia, through participatory approaches for sustainable local development. Focusing on the role of local leadership, the research investigates how community capacity can be enhanced to support inclusive decision-making, social cohesion, and resilient household livelihoods. The study evaluates the effectiveness of community-based economic empowerment programs in improving household welfare, income generation, and local resource utilization across three villages in Maluku: Morela Village (Leihitu District, Central Maluku Regency), Negeri Lima (Central Maluku Regency), and Namrole Village (Buru Selatan District). These sites were purposively selected because they actively implement participatory empowerment programs related to local resource management and customary governance, while varying in their geographic settings, program types, and institutional arrangements. The study further examines innovative public administration practices that facilitate collaboration between government agencies and non-governmental organizations (NGOs), with particular attention to how such collaboration promotes transparent and responsive governance. A convergent mixed-methods design was employed, combining semi-structured qualitative interviews with 15 local and customary leaders and 12 village government officials and NGO staff, four weeks of participatory observation, and structured quantitative surveys administered to 180 community members using validated empowerment indicators (Cronbach's α = 0.83). Qualitative data were analyzed thematically, while quantitative data were examined through descriptive statistics and bivariate correlation. Findings indicate that participatory strategies, when coupled with strong local leadership and adaptive administrative innovation, significantly contribute to sustainable development outcomes, including an increase in the social capital index from 3.2 to 4.1 on a five-point scale, a mean household income increase of 18% (from IDR 1,350,000 to IDR 1,593,000 per month), and improved community well-being. The study also identifies elite capture as a persistent risk in beneficiary selection at one research site, underscoring the need for transparent accountability mechanisms. Integration of local wisdom practices, particularly the customary sasi resource management system and village deliberation forums (musyawarah), strengthened program legitimacy and community ownership. The study offers practical implications for policymakers and development practitioners designing inclusive, accountable, and scalable empowerment programs in Maluku and comparable regional contexts. Keywords: community empowerment, local leadership, sustainable development, public administration innovation.